KAJIAN ENERGI KEMOREAKSI KAPUR API UNTUK PENGERINGAN BENIH CABE MERAH - Elisa Julianti; Soewarno T. Soekarto; Purwiyatno Hariyadi; Atjeng M. Syarief (Jurnal Keteknikan Pertanian, 2007)
ABSTRACT This research was aimed to study the energy potential of quicklime stone chemoreaction for the application to drying process of red chilli seeds. The experiment demonstrated that chemoreaction energy released from wafer reaction with CaO containing lime stone could be used for drying process of chilli seeds at ambient temperature to a very low moisture, varying of 2.5 - 3.7 % wb. The chemoreaction energy released from reaction between lime stone and plane water was 1.06 kJ/g lime stone. At excessive water condition partcle sizes of lime stone did not affect chemoresctton energy. but smstter size psttictes enhanced tile energy release from the reaction. Using three particle sizes of lime stone the energy efficiency for drying of red chilli seeds ranged 54.0 - 64.0 % and for plane water evaporation ranged 57.4 – 71.6 %. The energy effectiveness for chilli seeds drying was 4.7 kJ/g water and for plane water evaporation was 4.1 kJ/g, implying the presence of bound water in the chilli seeds. Diterima: 1 Juni 2006; Disetujui: 21 Maret 2007